Analisis Pengaruh Modal Usaha Lama Usaha Dan Lokasi Terhadap Pendapatan Pedagang Pada Pasar Tradisional Di Desa Alor Kecil Kecamatan Alor Barat Laut Kabupaten Alor - Sardian Sardian (Jurnal Ilmiah Wahana Pendidikan, 2023)
Income is the maximum value that can be consumed by traditional market traders in Alor Kecil Village in a period by expecting the same condition at the end of the period as the previous situation. The purpose of this study was to determine the effect of business capital, length of business and location on the income of traditional market traders in Alor Kecil Village, Northwest Alor District, Alor Regency. This type of research is a quantitative description. Samples were taken using accidential sampling technique. The sample in this study were 80 traders. Data collection tools used are observation, interviews, and literature studies. The data analysis model used to answer the hypothesis is multiple analysis, t test, F test. This research instrument test is used to measure the level of validity, reliability and classic assumptions from the answers to the research questionnaire. Based on the results of the validity test for each variable with a Pearson correlation value ≥ 0.3, the results of the validity test for each variable are declared valid. The reliability test results for each variable with a Crobatc Alpha value ≥ 0.6, the reliability test results for each variable are declared reliable. Kolmogrov-Smirnov Normality test results with sig. ≥ 0.05 then the test results are declared normal. The results of the heteroscedasticity test showed that the value of each independent variable was > 0.05, so there was no heteroscedasticity in this study. The results of the multicollinearity test show that the VIF value > tolerance means that multicollinearity does not occur in this study. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity value is > 0.05, so there is a relationship between the dependent variable and the independent variable. The analytical method used is multiple linear regression analysis technique. The results with the t test to answer the first, second, and third hypotheses, while multiple linear regression analysis simultaneously used the F test to determine the fourth hypothesis, namely to determine the effect of business capital, length of business and location on the income of traditional market traders in Alor Kecil Village, District Alor Northwest Alor District. Based on the calculation results of multiple linear regression analysis partially and simultaneously obtained a significance value of the Business Capital variable of 0.000, the length of business variable is 0.000, the location variable is 0.026, and the simultaneous effect of the value of the significance test F is 0.000b, the results of the t-test test and the F test is smaller than alpha (0.05), then the hypothesis testing proposed in this study is as follows: There is an influence of business capital, length of business and location on the income of traditional market traders in Alor Kecil Village, Alor Barat Laut District, Alor Regency .